Peningkatan Kemampuan Berpikir Kritis pada Pelajaran Matematika Siswa Kelas VI SD Citarik III melalui Model Pembelajaran Kooperatif Tipe Jigsaw - Chandra Sagul Haratua; Yuli Parlina; Mila Karmila; Bambang Mokhamad Akbar (Lembag, 2024)
This study aims to evaluate the effectiveness of the Jigsaw cooperative learning model in improving critical thinking skills in mathematics lessons for sixth-grade students at Citarik III Elementary School. The research was conducted using a two-cycle action research approach. The subjects of the study were 30 sixth-grade students at Citarik III Elementary School. Research instruments included pre-tests, post-tests, observation sheets, interviews, and field notes. The results showed that the Jigsaw learning model was effective in improving students' critical thinking skills. There was a significant increase in post-test scores in each cycle, indicating a progressive improvement in students' critical thinking skills. Good interaction among students in groups, positive student responses, and adjustments to lesson plans based on reflections from the previous cycle were key factors in the success of this learning model.